2004
DOI: 10.1348/0144666042037944
|View full text |Cite
|
Sign up to set email alerts
|

Of bikers, teachers and Germans: Groups' diverging views about their prototypicality

Abstract: The in-group projection model hypothesizes that members of social groups generalize attributes of their in-group to a superordinate category that provides dimensions for comparisons between in-group and out-group (in-group projection). As a result, both groups in an intergroup situation should disagree about their relative prototypicality for the superordinate category. Three studies confirmed this prediction. In Study 1 (N = 54), it was found that different groups of motor bikers (chopper-bikers vs. sport-bik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 36 publications
5
123
0
1
Order By: Relevance
“…It is this third suggestion which we address in this paper, although it is important to stress strongly and from the outset that we (like Waldzus et al, 2004) see the various explanations as complementary rather than competing. Our perspective fits with a growing body of work on group action which suggests that we need to consider not only the cognitive and motivational processes which create the instigation to behave in particular ways but also the instrumental considerations which shape the public expression of behavior -the so called SIDE perspective (Social Identity model of Deindividuation Effects) named after its origins in the analysis of anonymity and visibility on group action (for reviews, see Klein, Spears & Reicher, 2007;Postmes, Spears, Lea, & Reicher, 2000;Reicher, Spears, & Postmes, 1995).…”
Section: Accepted Manuscriptmentioning
confidence: 82%
See 3 more Smart Citations
“…It is this third suggestion which we address in this paper, although it is important to stress strongly and from the outset that we (like Waldzus et al, 2004) see the various explanations as complementary rather than competing. Our perspective fits with a growing body of work on group action which suggests that we need to consider not only the cognitive and motivational processes which create the instigation to behave in particular ways but also the instrumental considerations which shape the public expression of behavior -the so called SIDE perspective (Social Identity model of Deindividuation Effects) named after its origins in the analysis of anonymity and visibility on group action (for reviews, see Klein, Spears & Reicher, 2007;Postmes, Spears, Lea, & Reicher, 2000;Reicher, Spears, & Postmes, 1995).…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…However, in addition to the motivational account, Waldzus et al (2004) mention that there are two other ways of explaining ingroup projection. One is cognitive.…”
Section: Levels Of Explanation For Subgroup Prototypicality Judgmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mummendey and Wenzel (1999;Wenzel, Mummendey, Weber, & Waldzus, 2003), for example, state that people tend to project, and consequentially perceive the ingroup and its characteristics as more prototypical of the superordinate category than the outgroup and its characteristics. Waldzus, Mummendey, Wenzel, and Boettcher (2004) have shown that when primary school and high school teachers are confronted, both sets of teachers rate the traits of their own group (vs. those of the outgroup) as being more typical of the superordinate category teachers. Similar findings have been found for other groups (e.g., bikers, university students, etc.).…”
Section: Targets Of Dehumanisation and Their Moderatorsmentioning
confidence: 99%